Vision on metal additive manufacturing: Developments, challenges and future trends - Bernard, Alain; Kruth, Jean Pierre; Cao, Jian; Lanza, Gisela; Bruschi, Stefania; Merklein, Marion; Vaneker, Tom; Schmidt, Michael; Sutherland, John W.; Donmez, Alkan; da Silva, Eraldo J. (CIRP Journal of Manufacturing Science and Technology, 2023)
Additive Manufacturing (AM) is one of the innovative technologies to fabricate components, parts, assemblies or tools in various fields of application due to its main characteristics such as direct digital manufacturing, ability to offer both internal and external complex geometries without additional cost, and the potential of varying materials at the voxel level. However, despite high anticipations, AM as a real revolution for serial production of metal components has yet to be seen, mostly due to lacks of fundamental understanding, design engineering tools, and the global robustness of the value chains. This paper aims to provide a vision about the future of metal AM based on the collective knowledge of all ten scientific and technical committees of the International Academy of Production Engineering (CIRP).
CRIS-Team Scopus Importer:2024-12-16
Keywords: 3D printing; Additive Manufacturing; Innovative manufacturing technologies; Metal AM processes